Visualizing the blind brain: brain imaging of visual field defects from early recovery to rehabilitation techniques - Urbanski, Marika; Coubard, Olivier A.; Bourlon, Clémence (Frontiers in Integrative Neuroscience, 2014)
Visual field defects (VFDs) are one of the most common consequences observed after brain injury, especially after a stroke in the posterior cerebral artery territory. Less frequently, tumours, traumatic brain injury, brain surgery or demyelination can also determine various visual disabilities, from a decrease in visual acuity to cerebral blindness. VFD is a factor of bad functional prognosis as it compromises many daily life activities (e.g., obstacle avoidance, driving, and reading) and therefore the patient’s quality of life. Spontaneous recovery seems to be limited and restricted to the first six months, with the best chance of improvement at one month. The possible mechanisms at work could be partly due to cortical reorganization in the visual areas (plasticity) and/or partly to the use of intact alternative visual routes, first identified in animal studies and possibly underlying the phenomenon of blindsight. Despite processes of early recovery, which is rarely complete, and learning of compensatory strategies, the patient’s autonomy may still be compromised at more chronic stages. Therefore, various rehabilitation therapies based on neuroanatomical knowledge have been developed to improve VFDs. These use eye-movement training techniques (e.g., visual search, saccadic eye movements), reading training, visual field restitution (the Vision Restoration Therapy, VRT), or perceptual learning. In this review, we will focus on studies of human adults with acquired VFDs, which have used different imaging techniques (Positron Emission Tomography: PET, Diffusion Tensor Imaging: DTI, functional Magnetic Resonance Imaging: fMRI, MagnetoEncephalography: MEG) or neurostimulation techniques (Transcranial Magnetic Stimulation: TMS; transcranial Direct Current Stimulation, tDCS) to show brain activations in the course of spontaneous recovery or after specific rehabilitation techniques.